Numerical analysis of the vibration response of skew magneto-electro-elastic plates based on the higher-order shear deformation theory. (15th April 2019) - Vinyas, M.; Nischith, G.; Loja, M.A.R.; Ebrahimi, F.; Duc, N.D.
Abstract: This work addresses the problem of the three-dimensional free vibration behavior of skew magneto-electro-elastic plates under the framework of a higher order shear deformation theory. To this end, the finite element method was adopted considering the Hamilton's principle. The results obtained from the present finite element model are verified with the simulation results of COMSOL software. Further, a parametric study is carried out to evaluate the influence of boundary conditions, stacking sequence, aspect ratio, and the length-to-width ratio. A special emphasis has been given to the natural frequency characteristics of multiphase skew magneto-electro-elastic plates as well. The results from the present analyses allow concluding on the significant influence that the geometrical skewness has on the free vibration behavior of these plates.